GE_GERICHTE P/24054/2019 vom 20. Februar 2025 - GE Cour de justice (2025)
DISPOSITIONS PÉNALES DE LA LEI;USAGE DE FAUX(DROIT PÉNAL);VOL(DROIT PÉNAL);TENTATIVE(DROIT PÉNAL) | CP.139.ch1; LEI.118.al1; CP.22.al1